Avadomide plus obinutuzumab in patients with relapsed or refractory B-cell non-Hodgkin lymphoma (CC-122-NHL-001): a multicentre, dose escalation and expansion phase 1 study. Issue 9 (September 2020) - Michot, Jean-Marie; Bouabdallah, Reda; Vitolo, Umberto; Doorduijn, Jeanette K; Salles, Gilles; Chiappella, Annalisa; Zinzani, Pier Luigi; Bijou, Fontanet; Kersten, Marie José; Sarmiento, Rafael; Mosulen, Silvia; Mendez, Cristina; et al.
Summary: Background: Avadomide (CC-122) is a novel oral cereblon-modulating agent with promising activity in non-Hodgkin lymphoma. We aimed to examine the safety and preliminary activity of avadomide plus obinutuzumab in patients with relapsed or refractory non-Hodgkin lymphoma. Methods: CC-122-NHL-001 was a phase 1b dose escalation and expansion study at eight sites in France, Italy, and the Netherlands. Eligible patients (aged ≥18 years) had histologically confirmed CD20-positive relapsed or refractory non-Hodgkin lymphoma, had an Eastern Cooperative Oncology Group performance status of 0 or 1, and had received previous treatment. In the dose expansion phase, only patients with previously treated relapsed or refractory follicular lymphoma (grade 1, 2, or 3a) were included. Avadomide was administered in escalating doses and two formulations: active pharmaceutical ingredient in capsule in 1·0 mg, 2·0 mg, 3·0 mg, and 4·0 mg doses and as formulated capsules in 3·0 mg and 4·0 mg doses orally once daily on days 1–5 followed by 2 days off (5–7-day schedule) every week of each 28-day cycle. Obinutuzumab 1000 mg was administered intravenously on days 2, 8, and 15 of cycle 1 and day 1 of cycles 2–8. Primary objectives were to determine the safety and tolerability, the non-tolerated dose, maximum tolerated dose, and recommended phase 2 dose (RP2D). All patients who received treatment were included in the safety analyses. Efficacy-evaluable patients completed at least one cycle of treatment and had baseline and at least one post-baseline assessment. The study is registered with ClinicalTrials.gov, NCT02417285 and EudraCT 2014-003333-26, and is ongoing. Findings: Between June 24, 2015, and Dec 5, 2018, 73 patients were enrolled and treated; 19 had diffuse large B-cell lymphoma, 53 follicular lymphoma, and one marginal zone lymphoma. Median follow-up was 253 days (IQR 127–448). The median number of previous anticancer regimens was three (IQR 2–4). The maximum tolerated dose and non-tolerated dose were not reached in the dose escalation phase. On the basis of safety and pharmacokinetic–pharmacodynamic data, the avadomide RP2D was established as 3·0 mg as formulated capsules on a 5–7-day schedule in combination with 1000 mg of obinutuzumab. Patients enrolled in the expansion cohort received the established RP2D of avadomide. Across all doses, three patients had dose-limiting toxicities; one patient treated at the RP2D had dose-limiting toxicity (grade 3 sepsis). The most common adverse events of grade 3 and above were neutropenia (41 [56%] of 73) and thrombocytopenia (17 [23%] of 73). 34 (47%) patients had serious adverse events, which were considered to be avadomide-related in 23 (32%) of 73 patients and obinutuzumab-related in 20 (27%) of 73 patients. Two treatment-related deaths occurred, one owing to tumour flare and one from acute myeloid leukaemia after study discontinuation. Interpretation: Avadomide plus obinutuzumab has a manageable toxicity, being a tolerable treatment option for most patients. Although the prespecified threshold for activity was not met in the trial, we believe that the preliminary antitumour activity of cereblon modulators plus next-generation anti-CD20 antibodies in heavily pretreated relapsed or refractory non-Hodgkin lymphoma warrants further investigation as a chemotherapy-free option in this setting. Funding: Celgene Corporation.